THE EFFECT OF LOVE OF MONEY, FOMO & SELF-CONTROL ON GENERATION Z PERSONAL FINANCIAL PLANNING WITH FINANCIAL LITERACY AS A MODERATING VARIABLE - Sulhan, Muhammad; Putri, Erlisa Viviantika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
In Indonesia, the significance of personal financial planning is growing as people recognize the importance of effective money management for achieving financial stability and securing their future. This quantitative study aims to explore the influence of love of money, FoMO, and self-control on the personal financial planning of Generation Z students, with financial literacy serving as a moderating variable. Data was collected using a questionnaire, specifically targeting students from UIN Malang's economics faculty who belong to Generation Z. The purposive sample consisted of 313 respondents. The collected data was analyzed using the Smart PLS 3.0 software, employing path analysis as the analytical approach. The findings suggest that financial literacy does not act as a mediating factor in the relationship between love of money, FoMO, and self-control on personal financial planning. However, both love of money and self-control demonstrate significant and positive effects on personal financial planning, albeit with varying degrees of influence. Based on these results, it is recommended that students focus on improving their financial literacy and regularly develop personalized financial plans to ensure effective and efficient financial management.